2015
DOI: 10.1200/jco.2015.61.5070
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Obstruction in Survivors of Childhood Cancer: A Report From the Childhood Cancer Survivor Study

Abstract: Purpose For adult survivors of childhood cancer, knowledge about the long-term risk of intestinal obstruction from surgery, chemotherapy, and radiotherapy is limited. Methods Intestinal obstruction requiring surgery (IOS) occurring 5 or more years after cancer diagnosis was evaluated in 12,316 5-year survivors in the Childhood Cancer Survivor Study (2,002 with and 10,314 without abdominopelvic tumors) and 4,023 sibling participants. Cumulative incidence of IOS was calculated with second malignant neoplasm, lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…There have been few studies examining the association of WART dose with toxicity; however, studies have found higher doses of radiation to the abdomen and pelvis correlates with greater long-term toxicity. 36,37 Future studies are needed to understand the optimal WART dose for patients with DSRCT that balance toxicity with achieving disease control. In one instance, maintenance pazopanib was added for a patient with toxicity that prevented completion of planned cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few studies examining the association of WART dose with toxicity; however, studies have found higher doses of radiation to the abdomen and pelvis correlates with greater long-term toxicity. 36,37 Future studies are needed to understand the optimal WART dose for patients with DSRCT that balance toxicity with achieving disease control. In one instance, maintenance pazopanib was added for a patient with toxicity that prevented completion of planned cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, these toxicities precluded some patients from completing planned adjuvant chemotherapy regardless of whether HIPEC was utilized. There have been few studies examining the association of WART dose with toxicity; however, studies have found higher doses of radiation to the abdomen and pelvis correlates with greater long‐term toxicity 36,37 . Future studies are needed to understand the optimal WART dose for patients with DSRCT that balance toxicity with achieving disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of laparoscopic surgery is a reduced risk of intestinal obstruction, which is critical for pediatric oncology patients, especially if they receive radiotherapy [ 25 ]. In our study, all patients in the laparoscopy group started oral feeding within 3 days after surgery and no patients presented symptoms of ileus.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to open operations, laparoscopy and thoracoscopy can minimize long-term effects by improving functional outcomes (eg, improved chest wall growth/function), limiting psychosocial impact (eg, smaller scars/less disfiguration), and minimizing the frequency of late complications (eg, late intestinal obstructions known to occur in 5% of children with abdominopelvic tumors). 40,41 In addition, advancements in limb salvage techniques, now possible in . 80% of cases of osteosarcoma at specialized centers, may improve long-term function for children with extremity tumors.…”
Section: Surgerymentioning
confidence: 99%